Lithium ion glass adsorbent and preparation method thereof
By using Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 complex to prepare lithium-ion glass adsorbents, the problems of difficulty in controlling and high defect rate in the production process of existing lithium-ion adsorbents are solved, and the efficient adsorption of lithium ions and the optimization of product performance are achieved.
Patent Information
- Application Number
- CN202510194122.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lithium ion adsorbents are difficult to control during the production process, and are prone to produce color impurities with high defect rates, and the preparation process is complex, making it difficult to achieve large-scale industrial production.
Lithium ion glass adsorbent was prepared by using Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 composite, and glass adsorbent with excellent adsorption performance was obtained through high-temperature homogenization treatment and tableting process.
It realizes efficient adsorption of lithium ions in lithium ion solution, significantly reduces the mass concentration of lithium ions, has excellent characteristics of transparency, good mechanical strength, chemical stability and thermal stability, and is suitable for the lithium battery industry.
Smart Images

Figure CN119657070A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion adsorption, and in particular to a lithium ion glass adsorbent and a preparation method thereof. Background Art
[0002] The core of lithium batteries lies in the adsorption and desorption process of lithium ions. Adsorption and desorption mainly involve the synergistic effect of four major components: cathode, anode, electrolyte and diaphragm. During the charging stage, lithium ions precipitate from the cathode material, pass through the electrolyte, and are finally adsorbed in the specific gaps of the anode material. At the same time, lithium ions combine with anions in the electrolyte to form lithium salts and release electrons to the circuit to complete the storage of charge. On the contrary, during the discharge stage, lithium ions detach from the anode material, pass through the electrolyte back to the cathode, and are adsorbed by the gaps in the cathode material. At this time, the lithium salt in the cathode recombines with the cations in the electrolyte to form lithium ions, and absorbs electrons from the circuit to release charge. The chemical reaction mechanism of adsorption and desorption not only provides lithium batteries with charging and discharging functions, that is, the storage and release of charge, but also serves as the basis for it as an energy storage device.
[0003] Currently, the existing Li + In adsorption technology, Corning Inc. of the United States disclosed its technical solution of using anhydrous sodium phosphate as a lithium ion adsorbent, through the reaction: Na3PO4+ 3LiNO3→Li3PO4+ 3NaNO3 to produce precipitation, but Li + The adsorption and re-production process is difficult to control and requires real-time monitoring. The precipitate produced will be deposited on the surface of the product, resulting in an increase in the defective rate. Chinese patent CN11333295B discloses a lithium ion adsorbent, whose raw materials include manganese dioxide, an activator and water. Manganese dioxide generally includes β-MnO2 and γ-MnO2. β-MnO2 and γ-MnO2 have a higher specific surface area and a larger pore structure, providing more adsorption sites and surface reaction activity, which is beneficial to the adsorption and storage of lithium ions, but β-MnO2 and γ-MnO2 will introduce color impurities. Chinese patent application CN118925657A discloses a lithium ion adsorbent, whose raw materials include a soluble aluminum salt AlCl3 and a soluble lithium salt LiCl. AlCl3 and LiCl solutions are mixed and then slowly added to a NaOH solution for reaction. While generating Al(OH)3, Li + It is embedded in the Al(OH)3 interlayer structure to form a LiCl·2Al(OH)3·nH2O complex, but NaOH has strong alkaline corrosiveness and the preparation process is relatively complicated, making it difficult to achieve large-scale industrial production.
[0004] Therefore, there is an urgent need for a lithium ion adsorbent with excellent lithium ion adsorption performance and clear and impurity-free, which has high application value and practical significance for the lithium battery industry. Summary of the invention
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a lithium ion glass adsorbent, the components of the lithium ion glass adsorbent are Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 composite.
[0006] As an implementable case, the raw materials for preparing the lithium ion glass adsorbent include Al2O3, SiO2, TiO2, ZrO2, Na2CO3, K2CO3, and CeO2.
[0007] Furthermore, the mass ratio of Al2O3, SiO2, TiO2, ZrO2, Na2CO3, K2CO3, and CeO2 is (5-10): (20-40): (3-10): (2-7): (15-35): (0.01-5): (0.01-0.05).
[0008] As an practicable example, the specific surface area of the lithium ion glass adsorbent is 5-20 cm 2 / g.
[0009] Furthermore, the specific surface area of the lithium ion glass adsorbent is 8-12 cm 2 / g.
[0010] As an implementable case, the average thickness of the lithium ion glass adsorbent is 0.3-1 mm.
[0011] Furthermore, the average thickness of the lithium ion glass adsorbent is 0.5-0.7 mm.
[0012] As an practicable example, the average area of the lithium ion glass adsorbent is 1.5-5 cm 2 .
[0013] Furthermore, the average area of the lithium ion glass adsorbent is 2-3 cm 2 .
[0014] As an implementable case, the glass transition temperature of the lithium ion glass adsorbent is 450-550°C.
[0015] After the lithium ion glass adsorbent provided by the present invention is applied to a lithium ion solution for 3 hours, the mass concentration of lithium ions in the lithium ion solution can be reduced by 20-33wt%.
[0016] A second aspect of the present invention provides a method for preparing a lithium ion glass adsorbent, comprising: S1. The prepared raw materials are broken up by a ball mill, mixed evenly, and then subjected to high-temperature homogenization treatment to obtain glass liquid; S2, pressing the glass liquid into sheets using a high temperature resistant roller machine to obtain glass sheets; S3. Wash the glass slice to remove surface impurities, thereby obtaining a lithium ion glass adsorbent.
[0017] As an implementable case, the temperature of the high temperature homogenization treatment is 1500-1650°C.
[0018] As an implementable case, the high temperature homogenization treatment time is 2-3 hours.
[0019] As an implementable case, the washing includes pure water washing and organic solvent washing.
[0020] As an implementable example, the organic solvent includes alcohol.
[0021] The lithium ion adsorption principle of the lithium ion glass adsorbent provided by the present invention is based on a dynamic-separation-adsorption method, which can absorb Li in a solution with a flow property. + In the presence of Li + In the solution, Li + The concentration of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 glass is high, and Li + The diameter is smaller than the inner size of the crystal cavity of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 glass. The crystal cavity of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 glass has a large Li + It has strong polarity and Coulomb field, and has strong + Shows strong attraction, thus speeding up Li + Move towards the low concentration Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 glass to achieve Li + Highly efficient adsorption.
[0022] Specifically, the main substance in the lithium ion glass adsorbent provided by the present invention is Al2O3, which can improve the water resistance and temperature resistance of the lithium ion glass adsorbent, and is not easy to absorb moisture, which is convenient for the storage and transportation of the product. However, the amount of Al2O3 added should not be too much. If excessive amount is used, the melting temperature of the raw material needs to be increased to about 1700°C before it can be melted, which will also lead to excessive viscosity of the glass liquid, difficulty in rolling process, increased product thickness, and the presence of insoluble Al2O3 in the middle of the glass. SiO2 is the main structural skeleton of Al2O3- SiO2- TiO2- ZrO2- Na2O- K2O- CeO2 lithium ion glass adsorbent, which can make the lithium ion glass adsorbent have the characteristics of high transparency, good mechanical strength, chemical stability and good thermal stability; Na2O and K2O are fluxes for melting lithium ion glass adsorbent, which are mainly formed by removing a molecule of CO2 from the raw materials Na2CO3 and K2CO3 at high temperature. Na2O and K2O can reduce the melting temperature of lithium ion glass adsorbent, and the CO2 produced by decomposition at high temperature can increase the specific surface area of Al2O3- SiO2- TiO2- ZrO2- Na2O- K2O- CeO2 glass and increase the lithium ion exchange capacity of Al2O3- SiO2- TiO2- ZrO2- Na2O- K2O- CeO2. However, the dosage of Na2CO3 and K2CO3 should not be too much, otherwise it will cause Al2O3- SiO2- TiO2- ZrO2- The chemical properties of Na2O- K2O- CeO2 lithium ion glass adsorbent are unstable and easily absorb water and moisture; TiO2 and ZrO2 can improve the mechanical properties and high temperature resistance of lithium ion glass adsorbent. At the same time, TiO2 and ZrO2 can also act as nucleating agents to promote the formation of crystal nuclei in lithium ion glass adsorbents, thereby improving the mechanical strength and hardness of the product, making the lithium ion glass adsorbent have higher wear resistance and durability, and can be suitable for application scenarios with high strength and high wear resistance requirements; CeO2 can adjust the color change caused by residual iron ion impurities in industrial raw materials, and decolorize the green or blue color of lithium ion glass adsorbent caused by iron ion impurities. However, the addition amount of CeO2 also needs to be further limited. The addition amount of CeO2 is usually controlled at 0.05-0.1wt% of the weight of the raw material of lithium ion glass adsorbent. When the addition amount is too much, CeO2 particles may "agglomerate", resulting in a decrease in the specific surface area of the lithium ion glass adsorbent, thereby reducing Li + Adsorption performance.
[0023] Beneficial Effects (I) The lithium ion glass adsorbent provided by the present invention can significantly reduce the mass concentration of lithium ions in the solution by 20-33wt% within 3 hours after being applied to a solution containing lithium ions. The product has excellent lithium ion adsorption efficiency and performance.
[0024] (ii) The lithium ion glass adsorbent prepared by the present invention through a specific component ratio and preparation process has excellent properties of high transparency, good mechanical strength, chemical stability and thermal stability. The lithium ion glass adsorbent can maintain stable adsorption performance under various environmental conditions and extend its service life.
[0025] (III) The lithium ion glass adsorbent provided by the present invention improves the water resistance and temperature resistance of the product due to the addition of Al2O3, making the lithium ion glass adsorbent less likely to absorb moisture and convenient for storage and transportation.
[0026] (IV) The lithium ion glass adsorbent provided by the present invention can adjust the color change caused by the iron ion impurities in the industrial raw material due to the addition of CeO2, so the lithium ion glass adsorbent is more beautiful in appearance and also helps to improve the market competitiveness of the product.
[0027] (V) The preparation process of the lithium ion glass adsorbent provided by the present invention is relatively simple, including steps such as breaking up the raw materials, high temperature homogenization treatment, tableting and washing; by adjusting the preparation parameters such as the temperature and time of the high temperature homogenization treatment, and the washing method, the performance and preparation efficiency of the product can be further optimized. In addition, the specific component ratio also makes it easier to implement the lithium ion glass adsorbent in the roller pressing process, which is conducive to the industrial production of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a microscopic schematic diagram of the lithium ion glass adsorbent product prepared in Comparative Example 2. DETAILED DESCRIPTION
[0029] Example 1 In a first aspect of this example, a lithium ion glass adsorbent for lithium ion adsorption is provided, wherein the composition of the lithium ion glass adsorbent is a composite of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2.
[0030] The raw materials for preparing the lithium ion glass adsorbent are calculated by weight: 5 parts of Al2O3, 25 parts of SiO2, 7 parts of TiO2, 5 parts of ZrO2, 25 parts of Na2CO3, 1.85 parts of K2CO3, and 0.05 parts of CeO2.
[0031] The second aspect of this example provides a method for preparing a lithium ion glass adsorbent for lithium ion adsorption, specifically: S1. The prepared raw materials are broken up by a ball mill, mixed evenly, placed in a platinum crucible, and subjected to high-temperature homogenization treatment at 1500° C. for 3 h to obtain glass liquid; S2, pressing the glass liquid into sheets using a high temperature resistant roller machine to obtain glass sheets; S3. Wash the glass slice with pure water first, and then with alcohol to remove surface impurities, thereby obtaining a lithium ion glass adsorbent.
[0032] The specific surface area of the lithium ion glass adsorbent is 14.400 cm 2 / g, average thickness is 0.55mm, average area is 2.2cm 2 , the glass transition temperature (Tg) is 500℃.
[0033] Example 2 In a first aspect of this example, a lithium ion glass adsorbent for lithium ion adsorption is provided, wherein the composition of the lithium ion glass adsorbent is a composite of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2.
[0034] The raw materials for preparing the lithium ion glass adsorbent are calculated by weight: 6 parts of Al2O3, 25 parts of SiO2, 6 parts of TiO2, 5 parts of ZrO2, 28 parts of Na2CO3, 1.85 parts of K2CO3, and 0.05 parts of CeO2.
[0035] The second aspect of this example provides a method for preparing a lithium ion glass adsorbent for lithium ion adsorption, specifically: S1. The prepared raw materials are broken up by a ball mill, mixed evenly, placed in a platinum crucible, and subjected to high temperature homogenization treatment at 1500° C. for 3 h to obtain glass liquid; S2, pressing the glass liquid into sheets using a high temperature resistant roller machine to obtain glass sheets; S3. Wash the glass slice with pure water first, and then with alcohol to remove surface impurities, thereby obtaining a lithium ion glass adsorbent.
[0036] The specific surface area of the lithium ion glass adsorbent is 13.29 cm 2 / g, average thickness is 0.60mm, average area is 2.3cm 2 , the glass transition temperature (Tg) is 498℃.
[0037] Example 3 In a first aspect of this example, a lithium ion glass adsorbent for lithium ion adsorption is provided, wherein the composition of the lithium ion glass adsorbent is a composite of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2.
[0038] The raw materials for preparing the lithium ion glass adsorbent are calculated by weight: 7 parts of Al2O3, 23 parts of SiO2, 6 parts of TiO2, 6 parts of ZrO2, 26 parts of Na2CO3, 1.85 parts of K2CO3, and 0.05 parts of CeO2.
[0039] The second aspect of this example provides a method for preparing a lithium ion glass adsorbent for lithium ion adsorption, specifically: S1. The prepared raw materials are broken up by a ball mill, mixed evenly, placed in a platinum crucible, and subjected to high temperature homogenization treatment at 1550° C. for 3 h to obtain glass liquid; S2, pressing the glass liquid into sheets using a high temperature resistant roller machine to obtain glass sheets; S3. Wash the glass slice with pure water first, and then with alcohol to remove surface impurities, thereby obtaining a lithium ion glass adsorbent.
[0040] The specific surface area of the lithium ion glass adsorbent is 10.20 cm 2 / g, average thickness is 0.80mm, average area is 2.2cm 2 , the glass transition temperature (Tg) is 510℃.
[0041] Comparative Example 1 In a first aspect of this example, a lithium ion glass adsorbent for lithium ion adsorption is provided, wherein the composition of the lithium ion glass adsorbent is a composite of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2.
[0042] The raw materials for preparing the lithium ion glass adsorbent are calculated by weight: 5 parts of Al2O3, 25 parts of SiO2, 7 parts of TiO2, 5 parts of ZrO2, 35 parts of Na2CO3, 1.85 parts of K2CO3, and 0.05 parts of CeO2.
[0043] The second aspect of this example provides a method for preparing a lithium ion glass adsorbent for lithium ion adsorption, specifically: S1. The prepared raw materials are broken up by a ball mill, mixed evenly, placed in a platinum crucible, and subjected to high-temperature homogenization treatment at 1300° C. for 3 h to obtain glass liquid; S2, pressing the glass liquid into sheets using a high temperature resistant roller machine to obtain glass sheets; S3. Wash the glass slice with pure water first, and then with alcohol to remove surface impurities, thereby obtaining a lithium ion glass adsorbent.
[0044] The specific surface area of the lithium ion glass adsorbent is 39.139 cm 2 / g, average thickness is 0.30mm, average area is 2.1cm 2, the glass transition temperature (Tg) is 450℃.
[0045] Comparative Example 2 In a first aspect of this example, a lithium ion glass adsorbent for lithium ion adsorption is provided, wherein the composition of the lithium ion glass adsorbent is a composite of Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2.
[0046] The raw materials for preparing the lithium ion glass adsorbent are calculated by weight: 15 parts of Al2O3, 25 parts of SiO2, 7 parts of TiO2, 5 parts of ZrO2, 35 parts of Na2CO3, 1.85 parts of K2CO3, and 0.05 parts of CeO2.
[0047] The second aspect of this example provides a method for preparing a lithium ion glass adsorbent for lithium ion adsorption, specifically: S1. The prepared raw materials are broken up by a ball mill, mixed evenly, placed in a platinum crucible, and subjected to high temperature homogenization treatment at 1700° C. for 3 h to obtain glass liquid; S2, pressing the glass liquid into sheets using a high temperature resistant roller machine to obtain glass sheets; S3. Wash the glass slice with pure water first, and then with alcohol to remove surface impurities, thereby obtaining a lithium ion glass adsorbent.
[0048] The specific surface area of the lithium ion glass adsorbent is 8.45 cm 2 / g, average thickness is 1.10mm, average area is 2.5cm 2 , the glass transition temperature (Tg) is 518℃.
[0049] The microscopic schematic diagram of the lithium ion glass adsorbent product prepared in this example is as follows Figure 1 As shown, Figure 1 The red circle part is the phenomenon of poor powder dispersion uniformity and white spots caused by excessive addition of Al2O3.
[0050] Among them, the glass transition temperature in Examples 1-3 and Comparative Examples 1-2 was tested using a synchronous thermal analyzer, the instrument model of the synchronous thermal analyzer was TA-SDT-650; the specific surface area was tested by the ratio of the volume area to the weight of the lithium ion glass adsorbent.
[0051] Comparative Example 3 This example provides a lithium ion adsorbent, which is anhydrous sodium phosphate.
[0052] Performance Testing 1. High temperature and high humidity aging test Test objects: lithium ion glass adsorbents provided in Examples 1-3 and Comparative Examples 1-2.
[0053] Test conditions: In an environment of 80°C and 100% humidity, the lithium ion glass adsorbent was immersed in water for 72 hours, and the appearance of the lithium ion glass adsorbent was observed for changes. A pH meter was used to test the pH value of the water after immersion. The test results are detailed in Table 1.
[0054] Table 1
[0055] It can be seen from the experimental results in Table 1 that if the temperature of the high-temperature homogenization treatment of the lithium-ion glass adsorbent is low during the preparation process, it will have a certain negative impact on the product's high temperature resistance, high humidity resistance, and aging resistance.
[0056] 2. Lithium ion adsorption performance experiment Test objects: the lithium ion glass adsorbents provided in Examples 1-3, Comparative Examples 1-2, and the lithium ion adsorbent provided in Comparative Example 3.
[0057] Test method: Add the adsorbent to a sodium nitrate aqueous solution containing lithium ions, heat to 400°C, and then keep warm for 3 hours to test the adsorption performance of lithium ions. The test results are detailed in Table 2.
[0058] Table 2
[0059] It can be seen from the experimental results in Table 2 that the lithium ion glass adsorbents provided by Examples 1-3 of the present invention have excellent lithium ion adsorption performance and no impurities appear after use. Compared with the use of single-component anhydrous sodium phosphate, the adsorption effect is more excellent.
Claims
1. A lithium ion glass adsorbent, characterized in that: The composition of lithium ion glass adsorbent is Al2O3-SiO2-TiO2-ZrO2-Na2O-K2O-CeO2 composite; The raw materials for preparing the lithium ion glass adsorbent include Al2O3, SiO2, TiO2, ZrO2, Na2CO3, K2CO3, and CeO2; Among them, the mass ratios of Al2O3, SiO2, TiO2, ZrO2, Na2CO3, K2CO3 and CeO2 are (5-10): (20-40): (3-10): (2-7): (15-35): (0.01-5): (0.01-0.05).
2. The lithium ion glass adsorbent according to claim 1, characterized in that: The specific surface area of the lithium ion glass adsorbent is 5-20cm 2 / g.
3. The lithium ion glass adsorbent according to claim 1, characterized in that: The average thickness of the lithium ion glass adsorbent is 0.3-1 mm.
4. The lithium ion glass adsorbent according to claim 1, characterized in that: The average area of the lithium ion glass adsorbent is 1.5-5cm 2 .
5. The lithium ion glass adsorbent according to claim 1, characterized in that: The glass transition temperature of the lithium ion glass adsorbent is 450-550°C.
6. A method for preparing the lithium ion glass adsorbent according to any one of claims 1 to 5, characterized in that: include: S1. The prepared raw materials are broken up by a ball mill, mixed evenly, and then subjected to high-temperature homogenization treatment to obtain glass liquid; S2, pressing the glass liquid into sheets using a high temperature resistant roller machine to obtain glass sheets; S3. Wash the glass slice to remove surface impurities, thereby obtaining a lithium ion glass adsorbent.
7. The method for preparing the lithium ion glass adsorbent according to claim 6, characterized in that: The temperature of the high temperature homogenization treatment is 1500-1650°C.
8. The method for preparing the lithium ion glass adsorbent according to claim 7, characterized in that: The high temperature homogenization treatment time is 2-3h.
9. The method for preparing the lithium ion glass adsorbent according to claim 6, characterized in that: The washing includes pure water washing and organic solvent washing.
10. The method for preparing the lithium ion glass adsorbent according to claim 9, characterized in that: The organic solvent includes alcohol.
Citation Information
Patent Citations
Glass-based articles having a hard film and a crack mitigating composite structure for retained article strength and scratch resistance
CN110914212A
CHEMICALLY STRENGTHENED Li ABSORBING GLASS AND METHOD FOR PRODUCTION OF CHEMICALLY STRENGTHENED GLASS USING THE SAME
JP2001130923A
Composition recovery method of molten salt composition, and production method of chemically strengthened glass
JP2022171448A
Cited By
Sodium ion adsorbent as well as preparation method and application thereof
CN121550954A